2020
DOI: 10.1177/0363546520919956
|View full text |Cite
|
Sign up to set email alerts
|

Association Between the Postoperative Condition of the Subscapularis Tendon and Clinical Outcomes After Superior Capsular Reconstruction Using Autologous Tensor Fascia Lata in Patients With Pseudoparalytic Shoulder

Abstract: Background: Superior capsular reconstruction (SCR) has been performed for irreparable rotator cuff tear and pseudoparalytic shoulder (PPS); however, poor clinical outcomes have occasionally been reported. Previous studies have shown that the cause of poor clinical results was mainly graft rupture; however, poor clinical outcomes have also been observed in some cases even though the graft was not ruptured. Hypothesis/Purpose: We hypothesized that the subscapularis (SSC) tendon would be an important factor affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 17 publications
(30 reference statements)
1
23
0
Order By: Relevance
“…2). This preference aligns with current literature as a recent study by Takayama et al 36 investigated the importance of the condition of the subscapularis with SCR and found that flexion, abduction, and internal rotation were worse in patients with an irreparable subscapularis than in those with an intact or repairable subscapularis. Additionally, none of the patients with an irreparable subscapularis had reversal of pseudoparalysis after SCR.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…2). This preference aligns with current literature as a recent study by Takayama et al 36 investigated the importance of the condition of the subscapularis with SCR and found that flexion, abduction, and internal rotation were worse in patients with an irreparable subscapularis than in those with an intact or repairable subscapularis. Additionally, none of the patients with an irreparable subscapularis had reversal of pseudoparalysis after SCR.…”
Section: Discussionsupporting
confidence: 89%
“…Additionally, none of the patients with an irreparable subscapularis had reversal of pseudoparalysis after SCR. 36 In another study, Gilat et al 11 found that subscapularis tears were positively associated with clinical failure following SCR. Although improvements in patient-reported outcome measures and return to sports have been exhibited, these studies yield the importance of patient factors to treatment selection.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Failure of pseudoparalysis to resolve was associated with SCR graft tear. Subsequent studies by Takayama et al 32 and Burkart and Hartzler 4 also report the resolution of pseudoparalysis after autograft or allograft SCR.…”
Section: Editorialmentioning
confidence: 92%
“…In the setting of large to massive rotator cuff tears, pseudoparalysis has been linked to the extent of the tear and specifically to the involvement of the subscapularis. 4,7,10,32 In the July 2020 AJSM , Takayama et al 32 reported success using SCR to reverse pseudoparalysis, except in patients with irreparable subscapularis tears. In the December 2020 AJSM , Mihata et al 21 compared outcomes after SCR in patients with and without subscapularis tears.…”
mentioning
confidence: 99%